2013
DOI: 10.1007/s11144-012-0535-0
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of gaseous HCN in the presence of Ni-containing catalysts

Abstract: This work is devoted to the decomposition of gaseous HCN by oxidation with air catalyzed by different nickel containing catalysts. The presence of metallic nickel does not cause the decomposition of cyanide at 400°C, but NiO, electrochemical prepared nickel oxides Ni 2 O 3 ÁxH 2 O and (b,c)-NiOOH exhibit distinctly high catalytic activity at this temperature. The effect of HCN decomposition for electrochemically prepared nickel oxides was over 90 %. Nickel deposited on activated carbon also demonstrated cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…6, almost no HCN can be detected at 500 o C, indicating that Ni/LYLC is active enough for HCN decomposition at the temperature. The high activity of Ni/LYLC for HCN decomposition at 500 o C agrees well with the study by Osińska [25], who demonstrated the catalytic behavior of nickel catalyst for the destruction of HCN. The decomposition of Ntar and HCN at 500 o C mainly afforded NH3 and N2 in the yields higher than those from non-catalytic test.…”
Section: Nitrogen Distributionsupporting
confidence: 90%
“…6, almost no HCN can be detected at 500 o C, indicating that Ni/LYLC is active enough for HCN decomposition at the temperature. The high activity of Ni/LYLC for HCN decomposition at 500 o C agrees well with the study by Osińska [25], who demonstrated the catalytic behavior of nickel catalyst for the destruction of HCN. The decomposition of Ntar and HCN at 500 o C mainly afforded NH3 and N2 in the yields higher than those from non-catalytic test.…”
Section: Nitrogen Distributionsupporting
confidence: 90%
“…Al 2 O 3 for HCN decomposition at 400 o C agrees well with the study by Osińska[33], who demonstrated that a nickel catalyst is active for decomposing HCN. The decomposition of N WSO and HCN over Ni/Al 2 O 3 at 400 o C mainly formed NH 3 , affording a higher NH 3 yield compared to non-catalytic test.…”
supporting
confidence: 90%
“…In fact, hazardous gases such as CO, NO x and VOCs (volatile organic compounds) have been reported to interfere with human health and are one of the causes of some acute and chronic diseases. 2,3 Hydrogen cyanide (HCN) is a kind of highly poisonous gas and its toxicity is about 30 times that of CO. 4 Moreover, contact with HCN gas at a level of 500 ppm may lead to death in 15 min. 5 Thus, it is of great necessity to develop fast, steady and accurate devices for HCN gas detection so that we can obtain real-time information of HCN and take effective measures to ward off possible hazards.…”
Section: Introductionmentioning
confidence: 99%